Transfer Control of Public Housing Ownership in Indonesia - Muhammad Jibril; Alexandra Geradina Maretta (Jurnal Hukum Novelty, 2019)
Introduction to The Problem: Resettlement/Shelter is one of the basic human needs and plays a strategic role as the formation of character as well as national personality. However, there is still a problem concerning the availability of public housing in Indonesia. The root of this problem is because people are free to transfer their ownership over their public housing, which leads to the escalation of public housing price. One of the situations where an escalation of public housing price occurred and inaccurate-ownership is in Kalibata City. Kalibata City was supposed to be public housing, but in the present, it 3is occupied by upper-middle-income families as well as an investor.Purpose/Objective Study: The purpose of this research article is to observe, analyze, and criticize the transfer of public housing ownership in Indonesia and provide a comparison with the Community Land Trust in the United States of America.Design/Methodology/Approach: The research method employed in this research article is normative research method, whereas the types of data utilized are literature studies. The literature studies comprise of various sources in the form of laws, books, and journals related to public housing. The data is analyzed by employing a qualitative method and presented descriptively.Findings: The result of this research article indicates that the Government Regulation which is a follow-up to Article 55 paragraph (5) Law Number 1 of 2011 regarding Housing and Resettlement Area which mandates to regulate further related to the appointment and establishment of the institution has not been formed yet. Furthermore, to realize intergenerational justice, the transfer institution must be burdened with specific duties.